Chinks in the capitalism system - the pertinence of Islamic finance - Yahya, Mohamed Hisham; Muhammad, Junaina; Abdullah, Amalina; Md Nasir, Annuar (Academic and Business Research Institute, 2013)
Buying and selling occurs when a seller provides an item to a buyer at a price agreed by both parties. On the other hand, riba (usury or interest) is when someone gives a certain capital to another person with a condition that it is to be returned with a certain gain. Interest (usury), considered a taboo in Islam, has been one of the major causes of the financial crises in the West with the recent ones being the American subprime crisis and European sovereign debt crisis. What used to be the superpowers of modern finance have turned into indigent states. This paper compares both conventional and Islamic finance and looks at how Islamic finance can avoid the same mistakes from happening again. Islamic finance combines the divine and the secular with emphasis on spiritual values and social justice. In contrast to the western’s ‘Maximizing shareholders’ worth’ concept in finance, Islam states that profits in business must be accompanied with responsibility. It puts emphasis on profit sharing in lending funds. If one is not taking any business risks, he/she has no right to its profits. In a conventional banking system, due to the interest being charged, resources cannot be fully utilized as the funds available are discounted by interest fee. As such, usury is just not acceptable in Islam and would be destructive in any economic system.